Prevalence and patterns of opioid misuse and opioid use disorder among primary care patients who use tobacco. (1st January 2019) - John, William S.; Zhu, He; Mannelli, Paolo; Subramaniam, Geetha A.; Schwartz, Robert P.; McNeely, Jennifer; Wu, Li-Tzy
Highlights: We analyzed substance use in a large and diverse sample of primary care patients. Almost 9 of 10 primary care patients with opioid use disorder were tobacco users. More than 1 of 10 primary care patients who used tobacco reported opioid misuse. Opioid misuse was highest among tobacco users who were male and unemployed. We identified 3 latent classes of tobacco users according to polysubstance use. Abstract: Background: Current data suggest that opioid misuse or opioid use disorder (OUD) may be over represented among tobacco users. However, this association remains understudied in primary care settings. A better understanding of the extent of heterogeneity in opioid misuse among primary care patients who use tobacco may have implications for improved primary care-based screening, prevention, and intervention approaches. Methods: Data were derived from a sample of 2000 adult (aged ≥18) primary care patients across 5 distinct clinics. Among past-year tobacco users (n = 882), we assessed the prevalence of opioid misuse and OUD by sociodemographic characteristics and past-year polysubstance use. Latent class analysis (LCA) was used to identify heterogeneous subgroups of tobacco users according to past-year polysubstance use patterns. Multinomial logistic regression was used to examine variables associated with LCA-defined class membership. Results: Past-year tobacco use was reported by >84% of participants who reported past-year opioid misuse or OUD. Among those reporting past-year tobacco use, the prevalence of past-year opioid misuse and OUD was 14.0% and 9.5%, respectively. The prevalence of opioid misuse or OUD was highest among tobacco users who were male or unemployed. Three LCA-defined classes among tobacco users were identified including a tobacco-minimal drug use group (78.0%), a tobacco-cannabis use group (10.1%), and a tobacco-opioid/polydrug use group (11.9%). Class membership differed by sociodemographic characteristics. Conclusions: Results from this study support the benefit of more comprehensive assessment of and/or monitoring for opioid misuse among primary care patients who use tobacco, particularly for those who are male, unemployed, or polydrug users.